2016
DOI: 10.1590/s1806-37562016000000280
|View full text |Cite
|
Sign up to set email alerts
|

Tumor seeding along the needle track after percutaneous lung biopsy

Abstract: A 56-year-old male patient underwent percutaneous biopsy of a nodule in the right lung apex ( Figure 1A). The tip of a 19-gauge coaxial needle was positioned in the posterior chest wall ( Figure 1B), and six samples of the lesion were obtained with a 20-gauge core needle. The pathological analysis revealed squamous cell carcinoma. Using an anterior approach, we performed right upper lobectomy with tumor-free margins. At 6 months of follow-up, a positron emission tomography-CT scan of the chest showed an 18 F-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Tumor cell seeding after percutaneous needle biopsies can occur in various types of cancers [ 5 , 9 , 10 ]. In this study, we studied subcutaneously grown SKMEL2, a highly aggressive human melanoma xenograft, to test tumor seeding after core needle biopsy and the efficacy of GDS.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cell seeding after percutaneous needle biopsies can occur in various types of cancers [ 5 , 9 , 10 ]. In this study, we studied subcutaneously grown SKMEL2, a highly aggressive human melanoma xenograft, to test tumor seeding after core needle biopsy and the efficacy of GDS.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive review of the literature reveals that the observed incidence of tumor seeding after biopsy of hepatocellular carcinoma ranges from 0.6% to 5.1% of cases [25]. Furthermore, there have been reports of lung cancer tumor seeding with chest wall implantation in several documented cases [26,27]. Therefore, tract seeding is not unique to renal mass biopsy, and prior experience is largely anecdotal, with few reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate and diagnostic performance are the two main factors to consider when choosing a diagnostic procedure. Until now, several complications have been reported in patients underwent PNB, including pneumothorax, hemorrhage, tumor seeding, and air embolism . Pneumothorax and hemorrhage are the most two common complications, with reported frequencies of 17%‐26.6% and 4%‐27%, respectively .…”
Section: Discussionmentioning
confidence: 99%